2012
DOI: 10.15580/gjss.2012.1.gjss1204
|View full text |Cite
|
Sign up to set email alerts
|

Water Problems and Community Development: A Case Study of Igbo-Ora Community of Oyo State, Nigeria.

Abstract: Water is known to be an inexhaustible resource because the total supply of it in the biosphere is not affected by human activities. Recycling time depends on various factors. It is not uniformly distributed all over the world and not readily available in the quantity and quality required in most parts on the earth surface. This piece has examined the sources, the crisis of scarcity, and development of water and alternatives in Igbo-Ora, Nigeria. The climate is tropical continental. The major occupation is farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…It was also be gathered from Table 2, that the business grows till about 11 -15 years (50%), with a sharp decline over the last decade (25%) this could be attributed to water problems experienced in the region. Ikhile et al [12] reported that water scarcity is peculiar to this region. They stated that there are some rivers that surround and traverse the town.…”
Section: Fish Farming Experience In Ibarapamentioning
confidence: 93%
See 1 more Smart Citation
“…It was also be gathered from Table 2, that the business grows till about 11 -15 years (50%), with a sharp decline over the last decade (25%) this could be attributed to water problems experienced in the region. Ikhile et al [12] reported that water scarcity is peculiar to this region. They stated that there are some rivers that surround and traverse the town.…”
Section: Fish Farming Experience In Ibarapamentioning
confidence: 93%
“…On type of culture system it was found that monoculture system is commonly practiced and Clarias is popularly cultured amongst the farmers, probing further to seek the reason for the preference of Clarias fish, the fish was not cultured mainly for taste or survival rate rather it was chosen because of the hardy nature of fish to withstand unfavourable conditions, they would have gained due to experience gain over time in the business. It was also revealed that fish farmers source for water using the deep well (81.7%) as against bore-hole with (13.3), rivers accounted for only (5.0%) which aligns with the seasonal nature of the rivers [12] which makes it not dependable for all round aquaculture practice.…”
Section: Fish Farming Experience In Ibarapamentioning
confidence: 93%
“…Variations in climatic factors mostly rainfall and temperature correlate with crop production and yield in Nigeria (Adebayo, 1998;Tybee, 2006;Bello, 2010;Olanrewaju, 2009;Sawa and Adebayo, 2011;Mohammad et. al., 2011;Asikhia and Igbafen, 2012). The result of the above studies shows that climate variability is a threat to food security.…”
Section: Introductionmentioning
confidence: 99%